Landslide Susceptibility Classification of the Rerer Watershed, Minahasa Regency - Todingan, Melisa P.; Rahma S, Risal Nur; Umboh, Riel J.; Pakasi, Sandra E. (Jurnal Agroekoteknologi Terapan (JAT), 2026)
This study aims to analyze the level of landslide susceptibility in the Rerer Watershed, focusing on agricultural areas dominated by mixed gardens, dryland farms, and partially open land. The parameters used include slope gradient, rainfall, land use, soil type, and geology. The analysis employed a scoring method based on Geographic Information System (GIS) techniques to produce a susceptibility zonation map. The results show that the biophysical conditions of the Rerer Watershed are dominated by moderately steep slopes (15–25%), Eutropepts Dystrandepts soil types, and weathered volcanic rocks (Qtv), combined with an annual rainfall of approximately 1,500–2,000 mm. Anthropogenic factors, particularly agricultural cultivation on sloping terrain, significantly contribute to increased vulnerability. The landslide susceptibility zonation is classified into three levels: low (43.37 ha or 14.75%), moderate (230.17 ha or 78.27%), and high (20.53 ha or 6.98%). These findings emphasize the importance of implementing soil and water conservation strategies—such as terracing, cover crops, and agroforestry systems—to mitigate landslide risks while maintaining the hydrological sustainability of the Rerer Watershed in Minahasa Regency. Keywords: landslide susceptibility, agricultural land, watershed . Abstrak. Penelitian ini bertujuan menganalisis tingkat kerawanan longsor di DAS Rerer dengan fokus pada kawasan lahan pertanian yang didominasi kebun campuran, tegalan/ladang, dan sebagian lahan terbuka. Parameter yang digunakan meliputi kemiringan lereng, curah hujan, penggunaan lahan, jenis tanah, dan geologi. Analisis dilakukan dengan metode skoring berbasis Sistem Informasi Geografis (SIG) untuk menghasilkan zonasi kerawanan. Hasil penelitian menunjukkan bahwa kondisi biofisik DAS Rerer didominasi lereng agak curam (15–25%), jenis tanah Eutropepts Dystrandepts, serta batuan vulkanik (Qtv) yang mudah lapuk, dikombinasikan dengan curah hujan tahunan sekitar 1500-2000 mm/tahun. Faktor antropogenik berupa aktivitas budidaya lahan pertanian pada lereng miring menjadi pendorong utama peningkatan kerentanan. Zonasi kerawanan longsor terbagi dalam tiga kelas, yaitu rawan rendah seluas 43,37 Ha atau sekitar 14,75%, rawan sedang seluas 230,17 Ha atau sekitar 78,27%, dan rawan tinggi seluas 20,53 atau sekitar 6,98%. Temuan ini menegaskan pentingnya penerapan strategi konservasi tanah dan air, seperti terasering, vegetasi penutup, dan sistem agroforestri, guna mitigasi risiko longsor sekaligus menjaga keberlanjutan fungsi hidrologis DAS Rerer di Kabupaten Minahasa. Kata Kunci: rawan longsor, lahan pertanian, daerah aliran sungai